Current and Emerging Therapeutic Options for Gastroparesis - Myint, Aung S. (Gastroenterol Hepatol (N Y), 2018)
Gastroparesis is a complex, debilitating dysmotility disorder with challenging symptom management. A diagnosis of gastroparesis is based on objectively delayed gastric emptying in the absence of mechanical obstruction. Given the limited efficacy of treatment options and serious side effects, significant research continues for therapeutic options for gastroparesis. Promising investigational pharmacologic therapies include relamorelin, prucalopride, and aprepitant. A novel endoscopic therapy is gastric peroral endoscopic pyloromyotomy, which is associated with improved gastric emptying. This article reviews both current and emerging therapeutic options for gastroparesis, including dietary modification and pharmacologic, electrical stimulation, endoscopic, and surgical therapies. Further research and novel treatment options are needed to address the substantial morbidity of gastroparesis.